2016
DOI: 10.15386/cjmed-567
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Diffusion Sequence in Magnetic Resonance Imaging for the Differential Diagnosis between Hepatocellular Carcinoma and Benign Liver Lesions

Abstract: Background and aimTo assess the role of diffusion weighted imaging sequence (DWI), routinely used in hepatic magnetic resonance imaging (MRI) for the differentiation of hepatocellular carcinoma (HCC) from benign liver lesions.MethodsA number of 56 liver MRI examinations were retrospectively analyzed independently by two experienced radiologists, blinded to each other results. A total number of 70 Focal Liver Lesions (FLLs) assessed by liver MRI in 56 patients were included in the present study. All lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Lesion characterization: Several studies have attempted characterization of liver lesions using DW-MRI[ 33 - 38 ]. A general assumption is that ADC values are higher in benign lesions and lower in malignant liver lesions[ 33 - 36 ].…”
Section: Clinical Applications In Livermentioning
confidence: 99%
“…Lesion characterization: Several studies have attempted characterization of liver lesions using DW-MRI[ 33 - 38 ]. A general assumption is that ADC values are higher in benign lesions and lower in malignant liver lesions[ 33 - 36 ].…”
Section: Clinical Applications In Livermentioning
confidence: 99%
“…It has shown potential value in the characterization of benign and malignant liver nodules. [13][14][15] Moreover, recent studies have suggested that ADC may be useful in predicting histopathological differentiation, 16 microvascular invasion, 17 and early recurrence of HCC. 18 Among the quantitative ADC values, mean ADC (ADC mean ) is commonly selected.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in the past have stressed upon usefulness of ADC values in characterization of liver lesions but with significant difference of opinion. [6][7][8][9][10][11][12][13][14][15] In the present study no significant difference or bias was seen in various age groups or genders. Malignant lesions had a mean ADC of 1.13(x10 (−3) mm 2 /s), while benign lesions had mean ADC value of 1.63(x10 (−3) mm 2 /s) .…”
Section: Discussionmentioning
confidence: 64%
“…5 However, few other studies have reported that differentiation and characterization of focal lesions particularly solid benign lesion from malignant lesions such as focal nodular hyperplasia (FNH) from hepatocellular carcinoma (HCC) on the basis of ADC value is not completely reliable as both can show overlapping result. [6][7][8][9][10][11] In the absence of a reliable cut off value of ADC in differentiation of solid benign lesions from malignant lesions, this study aims to evaluate the role of diffusion weighted magnetic resonance imaging and quantification of ADC value in characterization of focal liver lesions and to determine a cut off value of ADC with cyto/histopathological correlation.…”
Section: Introductionmentioning
confidence: 99%